1994
DOI: 10.1063/1.355802
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of a rectifying junction at the interface between porous silicon and its substrate

Abstract: The current injection into metal/porous Si/bulk Si diodes is investigated by transport and photoresponse measurements. Under low forward bias, the diode current is determined by the space charge region at the porous Si/bulk Si interface. The activation energy of the photovoltage shows that holes are injected into porous Si states which have little quantum confinement. This is discussed in terms of the confinement model for porous Si photoluminescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…10 However, an interpretation of rectifying characteristics due to the junction between the PS and its Si substrate is also reported in the literature. 11 The present investigation reports results of dc measurements on PS/ p-Si structures sandwiched between two aluminum ͑Al͒ electrodes. The devices are biased at voltages less than 2.0 V. The range of voltages is important since the series resistance becomes a dominant factor for controlling current at relatively high voltages.…”
Section: Introductionmentioning
confidence: 99%
“…10 However, an interpretation of rectifying characteristics due to the junction between the PS and its Si substrate is also reported in the literature. 11 The present investigation reports results of dc measurements on PS/ p-Si structures sandwiched between two aluminum ͑Al͒ electrodes. The devices are biased at voltages less than 2.0 V. The range of voltages is important since the series resistance becomes a dominant factor for controlling current at relatively high voltages.…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for the low EL efficiency are not understood, but it has been suggested that the ease with which carriers are injected into luminescent states and the transport mechanisms in the porous silicon play an important role. 9 Much higher efficiencies were obtained using a liquid electrolyte junction which contacts the whole porous structure. [10][11][12] The mechanism of the strong visible emission from n-type porous silicon is thought to be similar to that for conventional semiconductors.…”
mentioning
confidence: 99%
“…This structure is inhomogeneous, consisting of ''bulk'' regions and ''quantum-sized'' crystallites. It has been argued that the minority carriers are injected preferentially into bulk regions, 9 which would account for the relatively low intensity of the emitted light. However, using electrolyte contacts there seems to be no problem with carrier injection into luminescent regions provided the energy levels in the solution are favourable.…”
mentioning
confidence: 99%
“…The electrical characteristics of metal/PS/c-Si/metal structures have been shown to exhibit similar rectifying features irrespective of the metal used for top contacts. Therefore, transport of carriers within the PS layer thickness and across the c-Si/PS hetero-junction governs the device characteristics [7]. Porous silicon photoconductors are commonly fabricated by depositing aluminum film on top of oxidized porous silicon structure.…”
Section: Introductionmentioning
confidence: 99%